2013
DOI: 10.1186/1756-0500-6-39
|View full text |Cite
|
Sign up to set email alerts
|

The zebrafish mutants for the V-ATPase subunits d, ac45, E, H and c and their variable pigment dilution phenotype

Abstract: BackgroundThe V-ATPase is a proton pump that creates an acidic medium, necessary for lysosome function and vesicular traffic. It is also essential for several developmental processes. Many enzymes, like the V-ATPase, are assemblies of multiple subunits, in which each one performs a specific function required to achieve full activity. In the zebrafish V-ATPase 15 different subunits form this multimeric complex and mutations in any of these subunits induce hypopigmentation or pigment dilution phenotype. We have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…The efficacy of atp6v0ca knockdown was confirmed at the genetic level (Figure S5A). Furthermore, knockdown larvae displayed characteristic pigment dilution (Figure S5B-C) as has been observed in insertional mutants of v-ATPase subunits [37]. It has been previously demonstrated in zebrafish that morpholino-mediated atp6v0ca knockdown results in inhibition of lysosomal acidification [38].…”
Section: Phagosomal Acidification Within Macrophages Issupporting
confidence: 61%
“…The efficacy of atp6v0ca knockdown was confirmed at the genetic level (Figure S5A). Furthermore, knockdown larvae displayed characteristic pigment dilution (Figure S5B-C) as has been observed in insertional mutants of v-ATPase subunits [37]. It has been previously demonstrated in zebrafish that morpholino-mediated atp6v0ca knockdown results in inhibition of lysosomal acidification [38].…”
Section: Phagosomal Acidification Within Macrophages Issupporting
confidence: 61%
“…It has been shown that V-ATPase is mostly found in acidic premelanosomes, but not in mature and highly pigmented melanosomes [ 93 ]. Moreover, several studies using zebrafish mutants in V-ATPase subunits strongly suggested that V-ATPase expression is required for melanosome biogenesis and/or to sustain normal melanosome morphology and stability [ 94 , 95 ]. Conceivably, the overexpression of Atp6v0d2 and other V-ATPase subunits in MGRN1-depleted cells might, therefore, be related with the increased number of melanosomes in these cells rather with the high specific activity of TYR in these melanosomes.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, mature melanosomes are transported from melanocytes to keratinocytes [43] . Furthermore, mutations in V-ATPase subunits produce pigment dilution phenotypes in Drosophila , zebrafish, mice and humans [44] , [45] . Since V-ATPase function has been shown to be essential for melanosome biogenesis, we hypothesize that the pigmented phenotype of CALM may be a consequence of increased expression of ATP6V0B and an increase in the number of mature melanosomes produced in melanocytes (or heightened pigmentation) and/or transported to surrounding keratinocytes.…”
Section: Discussionmentioning
confidence: 99%